Smiles or struggles? How trust (in)congruence influences subordinates’ ambivalent relational identification and upward ingratiation? - Ma, Xiaodong; Zhang, Minmin (Frontiers in Psychology, 2025)
Recent research on trust in organizational behavior has largely centered on perceived leader trust (PLT), shedding light on how being trusted influences employee behavior. However, this focus has often neglected expected leader trust (ELT)—employees’ internal expectations of being trusted—thus limiting insight into behavioral differences and the psychological mechanisms driven by trust discrepancies. To address this gap, the present study incorporates both ELT and PLT to provide a more holistic understanding of subordinates’ psychological dynamics and behavioral responses in trust relationships. Grounded in relational identity theory, we investigate how distinct trust configurations affect upward ingratiation (UI) and examine the mediating role of ambivalent relational identity (ARI). Employing a mediated Rising Ridge Congruence Asymmetry approach, we analyzed three-wave dyadic data from 330 supervisor–subordinate pairs. The findings reveal that: (1) UI is significantly lower when ELT and PLT are aligned; (2) When trust discrepancy is held constant, higher overall trust levels—particularly high ELT—are associated with increased UI; (3) Given the same average trust level and magnitude of discrepancy, UI is more pronounced when ELT exceeds PLT than when PLT exceeds ELT; (4) Across all trust configurations, ARI significantly mediates the relationship between ELT–PLT configurations and UI, indicating that identity conflict stemming from trust misalignment is a key psychological mechanism behind strategic ingratiation. This study extends the theoretical scope of trust research, offers deeper insight into its dynamic nature, and provides new empirical support for applying relational identity theory in trust-related contexts.